2014
DOI: 10.11113/jt.v70.2378
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on EIA process in Malaysia, West Australia, New Zealand and Canada

Abstract: The Environmental Impact Assessment (EIA) has become an essential tool in promoting sustainable development and environmental protection since it was formally introduced by National Environmental Policy (NEPA) in 1969. The acceptance and application of EIA as a key tool in ensuring green development was overwhelming and has reflected positive feedbacks since its first introduction to the world community. The implementation of the EIA in various countries differs from one another as each country customised thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In consequence to this Act, rising worldwide attention in sustainable development and environmental protection were received when the Environment Impact Assessment (EIA) were initiated especially in developed countries (Bhatia & Wernham, 2008;Bhatt & Khanal, 2010;Zhenxing & Hiufeng, 2010). Thus, EIA utilisation as worldwide policy transformation were adopted in over 120 countries for the development's decision-making (Cashmore, 2004;Glasson et al, 2005;Makmor and Ismail, 2014;Zhenxing and Hiufeng, 2010). The Environment Impact Assessment (EIA) is also known as an intercontinental pre-decision tool that integrates multidisciplinary participators that interact throughout the entire process in enhancing positive impacts and ensuring protection of the environment against the proposed development (Bastmeijer & Koivurova, 2008;Glasson et al, 2005;Peche & Rodríguez, 2009;Phillips, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In consequence to this Act, rising worldwide attention in sustainable development and environmental protection were received when the Environment Impact Assessment (EIA) were initiated especially in developed countries (Bhatia & Wernham, 2008;Bhatt & Khanal, 2010;Zhenxing & Hiufeng, 2010). Thus, EIA utilisation as worldwide policy transformation were adopted in over 120 countries for the development's decision-making (Cashmore, 2004;Glasson et al, 2005;Makmor and Ismail, 2014;Zhenxing and Hiufeng, 2010). The Environment Impact Assessment (EIA) is also known as an intercontinental pre-decision tool that integrates multidisciplinary participators that interact throughout the entire process in enhancing positive impacts and ensuring protection of the environment against the proposed development (Bastmeijer & Koivurova, 2008;Glasson et al, 2005;Peche & Rodríguez, 2009;Phillips, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Due to this matter, it has led multiple environmental issues to exist in this nation. According to Makmor and Ismail (2014), the public participation carried out under the First Schedule for EIA in Malaysia is often shallow and insignificant. Briffet et al (2004), Harun & Mazlan (2008), Makmor and Ismail (2016a), Marzuki (2009) and Li et al (2012) have concurred with evidences that shown most of the EIA reports of the First Schedule activities that were submitted and approved by the DOE without public participation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation